Improvement of students learning outcomes and motivation with chemical practicum e-module - Nelius Harefa; Novia Fransisca Dewi Silalahi (Jurnal Pendidikan Kimia (JPKim), 2020)
The use of modules has an effect on students’ motivation and students’ learning outcomes. Based on the analysis of learning outcomes data using paired sample t-test SPSS 21 shows that tcount (4.872)> ttable (2.354) at significance α = 0.05, which means that there are differences in students’ learning outcomes taught using chemistry practicum e-modules and practicum modules conventional. Students’ learning outcomes by utilizing the chemistry practicum e-modules are higher than students’ learning outcomes by utilizing conventional practicum modules. 93.24% of students have very strong motivation to study in the laboratory by utilizing the chemistry practicum e-module while by utilizing conventional practicum modules by 72.98%. Meanwhile, the Pearson Correlation test is 0.613 at significance α = 0.05, which means that there is a strong relationship between learning motivation and student learning outcomes. Keywords: Chemistry; e-module; learning outcomes; motivation; practicum